The Transmission of US Financial Stress: Evidence for Emerging Market Economies - Yves S. Schüler; Fabian Fink (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We provide empirical evidence that US financial stress shocks (US-FSSs) are an important driver for economic dynamics and fluctuations in emerging market economies (EMEs). Applying a structural vector autoregression, we analyze the international transmission of US-FSSs to eight EMEs using monthly data from 1999 to 2012. US-FSSs are identified as unexpected changes in the financial conditions index of the Federal Reserve Bank of Chicago. Findings indicate that a typical EME experiences similar negative effects as the US economy in response to US-FSSs. Our results emphasize that the transmission through international financial interconnections is dominant, while contagion through trade is inessential. Further, with regard to fluctuations in real economic activity, US-FSSs are as important as all other external factors jointly. In general, US-FSSs represent a crucial driver for volatility in the emerging world; also at business cycle frequencies.
Keywords: E44; F30; G10; 330